LEADERSHIP AND GENDER : WOMEN'S POLITICAL PARTICIPATION IN MALAYSIA (1980-2013) - Nor Rafidah, Saidon; Sity, Daud; Mohd, Samsudin (2019)
This study discusses the relationship between leadership and gender in women's political participation in Malaysia from 1980 to 2013. This study has tried to identify the factors for women's political participation and the relationship between leadership and gender in women's political participation in Malaysia. The aim is to show women's ability to manage leadership as elected representatives in their constituencies, political parties, community and country. This study also investigates the obstacles to women's political participation in Malaysia. Qualitative research method used are observation and interviews with 15 respondents selected amongst politicians and scholars who write about women's political participation. In addition, secondary data and information from past research are combined with primary sources in the qualitative analysis. The conceptual framework used in this study is a legalrational leadership theory and the concept of the social construction of gender. Finding shows that women's political participation is influenced by several factors that are identified as educational, economic, social, health and environment. The level of women's political participation takes place in stages due to some constraints such as education, culture, religion, social and other factors. The ability of women's leadership is not influenced by gender but it affects her leadership style. Female Members of Parliament are capable to perform their job as good as the male counterparts, as well as able to be knowledgeable of various issues and have a high level of political awareness.